2016
DOI: 10.1016/j.atherosclerosis.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging of atherosclerosis regression with magnetic resonance to guide drug development

Abstract: Slowing of progression and inducing the regression of atherosclerosis with medical therapy have been shown to be associated with an extensive reduction in risk of cardiovascular events. This proof of concept was obtained with invasive angiographic studies but these are, for obvious reasons, impractical for sequential investigations. Non-invasive imaging has henceforth replaced the more cumbersome invasive studies and has proven extremely valuable in numerous occasions. Because of excellent reproducibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…13 High spatial-resolution imaging of the carotid vessels is readily feasible, with accurate, reproducible measurements of carotid plaque thickness, volume and area derived from black-blood imaging sequences.…”
Section: Carotid Imagingmentioning
confidence: 99%
“…13 High spatial-resolution imaging of the carotid vessels is readily feasible, with accurate, reproducible measurements of carotid plaque thickness, volume and area derived from black-blood imaging sequences.…”
Section: Carotid Imagingmentioning
confidence: 99%
“…The joint ESC Guidelines suggested that early diagnosis of high-risk patients could be equally effective as preventing new cases, leading to potential cost-savings, and consequently encouraged research regarding risk assessment by non-or minimally invasive imaging techniques [3]. Techniques such as multi-detector CT [4,5], intravascular ultrasound [6,7], MRI [8,9], or Optical Coherence Tomography [10] are extensively being investigated for the assessment of morphological or structural characteristics of atherosclerotic lesions. Among the molecular imaging modalities, which can reveal specific biological aspects of atherosclerotic plaques, positron emission tomography/computed tomography (PET/CT) is one of the preferred techniques in clinic [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, timely and precise diagnosis and effective treatment are essential to delay the progression of the disease and to improve the survival rate. In comparison with other diagnostic methods, such as computed tomography (CT), ultrasonic imaging, and positron emission computed tomography (PET), magnetic resonance imaging (MRI) is widely used in clinical for its advantages of no invasion, no radiation and high soft tissue contrast in imaging [4,5]. Although the contrast agents such as iron and gadolinium agent increase the imaging effectiveness [6], MRI is still difficult to distinguish between small abnormal and normal tissues.…”
Section: Introductionmentioning
confidence: 99%